A defense of the paraconsistent approach to quantum superpositions (reply to Arenhart and Krause) - De Ronde, Christian (Universidad Nacional de Quilmes, 2019)
Fil: De Ronde, Christian. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina.